2014
DOI: 10.1108/jocm-05-2014-0103
|View full text |Cite
|
Sign up to set email alerts
|

The well-being of women at work: the importance of resources across the life course

Abstract: Purpose – The purpose of this paper is to explore the factors that impact on the well-being of women workers, as assessed through depression, anxiety and stress, across the life course, i.e. age, marital status and parental status. Design/methodology/approach – The quantitative study was cross-sectional in nature and used an online self-report questionnaire to generate information on job/work characteristics, belief systems and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…In drawing on the broaden-and-build theory, we provide evidence that positive-affect nurses are more likely to have the resources necessary to deep act toward patients. In addition, the conclusion based on the research sample of primarily female nurses echoes the argument that women require resources to maintain their well-being and performance outcomes (Gervais and Millear, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…In drawing on the broaden-and-build theory, we provide evidence that positive-affect nurses are more likely to have the resources necessary to deep act toward patients. In addition, the conclusion based on the research sample of primarily female nurses echoes the argument that women require resources to maintain their well-being and performance outcomes (Gervais and Millear, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Resources have been shown to improve on well-being and performance (see . Overall, the importance of resources has been raised in the literature continuously (see de Jonge, Bosma, Peter, & Siegrist, 2000 ;Gervais & Millear, 2014 ;. The relevance of psychosomatic symptoms as a predictor in organisational research was shown as it led to higher job strain (waves 1 and 2) and lower work performance (wave 2).…”
Section: Discussionmentioning
confidence: 99%
“…Another important variable that needs attention is the age of respondents. Literature shows that younger women with more family responsibilities need family-friendly employers' policies to cope with both work and nonwork activities (Gervais & Millear, 2014). Taking the above into account, the aim of this study is to answer the following research questions:…”
Section: Introductionmentioning
confidence: 99%